Modelling and Estimation of Credits with Dynamic Space-Time Panel Data Methods on the Basis of the Provinces in Turkish Commercial Banking Sector - (:unkn) unknown (INT BUSINESS INFORMATION MANAGEMENT ASSOC-IBIMA, 2015)
Dynamic space-time panel data method has been developed and it is increasingly used in the analysis of geographical firm data. In our study, the loans that opened in the basis of provinces in commercial banks operating in Turkey have been analysed with this method. Bank loans covering the period 1988-2013 and eighty provinces were modelled based on time and space on the basis of neighbourhood relationship. Dynamic analysis which is used two alternative estimators has yielded highly successful results. Findings revealed that a dynamic model based on space-time concept shows much better estimates comparing to an ordinary dynamic model.
Keywords: Bank credits; spatial dependence; dynamic space-time panel data models; GMM; MLE; UNIT-ROOT TESTS; SPATIAL COMPETITION; SPECIFICATION; POWER